Answer:
The correct option is B.
Step-by-step explanation:
The given function is
![f(x)=x^3](https://tex.z-dn.net/?f=f%28x%29%3Dx%5E3)
The translation of a function is defined as
![g(x)=f(x+a)+b](https://tex.z-dn.net/?f=g%28x%29%3Df%28x%2Ba%29%2Bb)
If a>0, then the graph of f(x) shift a units left and if a<0, then the graph of f(x) shift a units right.
If b>0, then the graph of f(x) shift b units up and if b<0, then the graph of f(x) shift b units down.
It is given that the graph of f(x) shifts 4 units left and 2 units down. So, a=4 and b=-2.
![g(x)=f(x+4)+(-2)](https://tex.z-dn.net/?f=g%28x%29%3Df%28x%2B4%29%2B%28-2%29)
![[\because f(x)=x^3]](https://tex.z-dn.net/?f=%5B%5Cbecause%20f%28x%29%3Dx%5E3%5D)
![y=(x+4)^3-2](https://tex.z-dn.net/?f=y%3D%28x%2B4%29%5E3-2)
Therefore option B is correct.
Answer:
amplitude; ![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
Phase shift;
units right
Period;![\frac{2\pi}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cpi%7D%7B3%7D)
Step-by-step explanation:
The given function is
![y=-\frac{2}{3}\cos(3t-3\pi)](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B2%7D%7B3%7D%5Ccos%283t-3%5Cpi%29)
This function is of the form;
![y=A\sin (Bt+C)](https://tex.z-dn.net/?f=y%3DA%5Csin%20%28Bt%2BC%29)
The period is given by:
![|A|=|-\frac{2}{3}|= \frac{2}{3}](https://tex.z-dn.net/?f=%7CA%7C%3D%7C-%5Cfrac%7B2%7D%7B3%7D%7C%3D%20%5Cfrac%7B2%7D%7B3%7D)
The period is given by:
![T=\frac{2\pi}{|B|}= \frac{2\pi}{|3|}=\frac{2\pi}{3}](https://tex.z-dn.net/?f=T%3D%5Cfrac%7B2%5Cpi%7D%7B%7CB%7C%7D%3D%20%5Cfrac%7B2%5Cpi%7D%7B%7C3%7C%7D%3D%5Cfrac%7B2%5Cpi%7D%7B3%7D)
The phase shift is given by;
or
units right.
Answer:
11.8845
Step-by-step explanation:
11.8845 to the up and down answer it will be down
Answer:
The equation of the line is,
![y = - \frac{2}{5} x - 1](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20x%20-%201)
Step-by-step explanation:
First, you have to write it in a form of y = mx + b :
![2x + 5y = 15](https://tex.z-dn.net/?f=2x%20%2B%205y%20%3D%2015)
![5y = 15 - 2x](https://tex.z-dn.net/?f=5y%20%3D%2015%20-%202x)
![y = 3 - \frac{2}{5} x](https://tex.z-dn.net/?f=y%20%3D%203%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20x)
![y = - \frac{2}{3} x + 5](https://tex.z-dn.net/?f=y%20%3D%20%20%20-%20%5Cfrac%7B2%7D%7B3%7D%20x%20%2B%205)
When both lines are parallel to each other, they will have to same gradient value. So the equation of the line is y = (-2/5)x + b. Next, you have to find the value of b by substutituting (-10,3) into the equation :
![y = - \frac{ 2}{5}x + b](https://tex.z-dn.net/?f=y%20%3D%20%20%20-%20%5Cfrac%7B%202%7D%7B5%7Dx%20%2B%20b%20)
![let \: x = - 10,y = 3](https://tex.z-dn.net/?f=let%20%5C%3A%20x%20%3D%20%20-%2010%2Cy%20%3D%203)
![3 = - \frac{2}{5} ( - 10) + b](https://tex.z-dn.net/?f=3%20%3D%20%20-%20%20%5Cfrac%7B2%7D%7B5%7D%20%28%20-%2010%29%20%2B%20b)
![3 = 4 + b](https://tex.z-dn.net/?f=3%20%3D%204%20%2B%20b)
![3 - 4 = b](https://tex.z-dn.net/?f=3%20-%204%20%3D%20b)
![b = - 1](https://tex.z-dn.net/?f=b%20%3D%20%20-%201)
Answer:
The standard form of the quadratic equation is x² + 3·x - 4 = 0
Step-by-step explanation:
The standard form of a quadratic equation is a·x² + b·x + c = 0
Given that the expression of the quadratic equation is (x + 4)·(x - 1) = y, we can write the given expression in standard form by expanding, and equating the result to zero as follows;
(x + 4)·(x - 1) = x² - x + 4·x - 4 = x² + 3·x - 4 = 0
The standard form of the quadratic equation is x² + 3·x - 4 = 0
The graph of the equation created with MS Excel is attached